Field notes contributed by Chris Edwards, fall 1993 - Edwards, Chriset al (1993)
Fall report of birds and locations contributed by Chris Edwards and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed